Postgrowth Control of the Interfacial Oxide Thickness in Semiconductor–Insulator–Semiconductor Heterojunctions. Issue 12 (18th April 2018) - Maman, Nitzan; Templeman, Tzvi; Manis‐Levi, Hadar; Shandalov, Michael; Ezersky, Vladimir; Sarusi, Gabby; Golan, Yuval; Visoly‐Fisher, Iris
Abstract: The electronic properties of the heterojunction formed by chemical bath deposition of a thorium‐ and oxygen‐doped PbS nanostructured layer on GaAs substrate as a function of postgrowth thermal treatments are studied. A correlation is found between the heterojunction conductance and the duration of thermal treatment in air. In contrast to previous reports on the effect of air annealing on PbS films, where the conductance increased due to oxygen incorporation within the PbS, in this oxygen‐saturated system, the PbS properties are unaffected by exposure to oxygen. Control over the heterojunction conductance is achieved by tuning the interface oxide thickness, enabled by thermal treatment in air, resulting in the elimination of Fermi level pinning caused by interface induced gap states. The ability to control the interfacial insulator thickness post film‐growth is a unique feature of this system. Abstract : The electronic properties of semiconductor–insulator–semiconductor junctions of thorium‐ and oxygen‐doped PbS thin films on GaAs are studied. Control over the conductance is achieved by tuning the interface oxide thickness, via thermal treatments in air, resulting in elimination of Fermi level pinning caused by interface induced gap states. The ability to control the interfacial insulator thickness post film growth is a unique feature.